Telework and the future of work and organizations – An Exploratory Analysis - Salavisa, I.; Simões, E.; Rebelo, G. (7º Workshop “Dinâmicas Socioeconómicas e Territoriais Contemporâneas”, DINÂMIA´CET, ISCTE-IUL, 2023)
The pandemic has dramatically accelerated the pace of the digital transformation underway (Schwab, 2016), drawing on a vast range of solutions based in telecommunications and ICT in work organization, services, sales, education and telemedicine. In this context, teleworking represented a major change that has not been fully reversed after the pandemic. In fact, homework continued to increase across European countries (ELFS, 2023), due to the confluence of workers’ preferences and business interests (Bathini & Kandathil, 2019). In the short term, in the aftermath of the pandemic, the hybrid model, combining presential and homework, seems to represent a realistic and well-regarded option both for many enterprises and for employees. However, medium-term impacts are less acknowledged, in both organizations and work, which are intimately intertwined. In fact, the extensive usage of digital technologies is changing business models, the shape of work organization and labour markets landscape, with the expansion of outsourcing and externalization of more and more activities. Companies aim to keep core activities only, and externalize the rest, in the line of the New Economy American firm (Lazonick, 2005). In this line, the hybrid model would represent an intermediate stage from the conventional hierarchical firm to a transactional configuration (Williamson, 1975).